MENINGKATKAN PARTISIPASI DAN HASIL BELAJAR SISWA KELAS X-A DALAM PENGUASAAN KONSEP PENGGOLONGAN HIDROKARBON DI SMA NEGERI I TANTA MELALUI MODEL PEMBELAJARAN KOLABORATIF STAD – MAKE A MATCH - Salasiah Salasiah (Universitas Lambung Mangkurat, 2012)
Implementation of collaborative learning model STAD-Make a match on the classification of hydrocarbons learning, was studiet. This study aims to (1) improve student’s participation and performance in learning chemistry (2) develop a chemistry learning activities that can stimulate students to learn more and (3) improve student learning outcomes. This study used action research class design with twice cycle. Research subjects were 23 students of class XA SMAN I Tanta Tabalong. The research instrument concist of written test objective and non-test instruments such as questionnaires and observation. This research concluded that (1) The use of collaborative learning model STAD - Make a match improved student participation XA SMAN I TANTA with excellent category in classification Hydrocarbon learning and stimulate students to learn more (2) student’s learning outcomes increased although not the constant in the second cycle, but does not affect the 100% mastery learning (3) learning with collaborative methods STAD - Make a match no longer focus only on teacher activity but make students more active in learning.Keywords: STAD, Make a match, student participation, learning outcomes, classification of hydrocarbons